Optical and structural characterisation of ultra-thin films - Skjonnemand, K. (Cranfield University, 2000)
Chloride, bromide, pyridinium and quinolinium homologues of 4-(N- hexadecylpyridinium-4-ylmethylidene-amino)-2,6-dichlorophenolate have been investigated in solution, Langmuir and Langmuir-Blodgett films. Techniques including spectroscopy, surface potential measurement, quartz crystal microbalance, surface plasmon resonance, atomic force microscopy, reectometry and X-ray diffraction have been used to characterise these molecular systems. In solution, solvatochroism was observed and Benisi-Hildebrand analysis revealed dimeric aggregation. Langmuir monolayers were compressed at the air/water interface and chromophore rotation was observed by surface potential measurement. Langmuir- Blodgett monolayers showed lm-thickness dependence on the deposition-pressure. Monolayer thicknesses between 6-24Ä were measured using SPR and molecular areas between 40-l25Ä2 were measured using a quartz crystal microbalance. Both the molecular/s/area)and monolayer thicknesses were deposition-pressure dependent. The high tilt phases were visually distinguishable from the low tilt phases using atomic force microscopy, The compounds showed phase behaviour that was predominantly alike for the bromide and chloride homologues but different for the pyridinium and quinolinum homologues. Multilayer Y-type films of the merocyanine dyes were analysed using reectometry and deposition-pressure dependent thicknesses were found. Alternate layer structures of NLO-active hemicyanine amphiphiles were used to achieve homogeneous. orientation ordering using active and inactive spacer layers. Ordering was achieved but the optical efficiency was reduced by high proportions of inactive material and interlayer dipole formation. Double chained hemicyanine molecules were used to form Z-type structures and subsequent layers were found to significantly interdigitate. Different chain lengths were found to interdigitate by the length of the shortest chain. Gas detection experiments were undertaken on the quinolinium, dichloro merocyanine using three optical geometries. The absorption method showed slow switching and poor sensitivity. The Kretschmann SPR geometry showed high sensitivity and rapid switching. The grating SPR geometry showed rapid switching but was less sensitive than the ATR method. Protonation of the monolayers was investigated using hydrochloric acid gas, acetic acid vapour and stearic acid immobilised within the lm.